Digestible lysine levels for laying hens and their effects on egg quality - Santos, Tiago Antônio Dos; Geraldo, Adriano; Machado, Luiz Carlos; Pelícia, Kléber; Simão, Sérgio Domingos; Vieira Filho, Javer Alves [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2014)
Egg quality of semi-heavy laying hens fed on low protein diets (14.0% CP) and on different lysine levels is evaluated, while maintaining the same ratio of digestible amino acids / digestible lysine. Four hundred and twenty commercial strain Isa Brown laying hens, 28 weeks old, were divided into 42 experimental plots. A completely randomized design with six treatments and seven replicates was employed in four production cycles of 28 days each. Treatments comprised Control - 16.92% CP; 0.750% digestible lysine. Treatments 1 to 5, with CP levels 14% and digestible lysine levels 0.600, 0.675, 0.750, 0.825 and 0.900% respectively. Levels of Treatments 1 and 2 (0.546 and 0.640% digestible Met + Cys / 0.600 and 0.675% digestible lysine) provided smaller egg size. On the other hand, eggs had higher shell percentage when compared to control diet. When compared to other digestible amino acids, digestible lysine requirement may be estimated at 0.750% in a diet with 14% CP, which corresponds to the average daily intake of 876 mg dig. lysine hen-1 day-1 and 798 mg dig. Met + Cys hen-1 day-1, without jeopardizing performance and eggs' internal and external quality.

A presente pesquisa objetivou avaliar a qualidade dos ovos de poedeiras semipesadas submetidas a dietas com baixa proteína (14,0% PB) e diferentes níveis de lisina, mantendo a mesma relação aminoácidos digestíveis/lisina digestível. Foram utilizadas 420 poedeiras da linhagem comercial Isa Brown, com 28 semanas de idade distribuídas em 42 parcelas experimentais. Foi utilizado um delineamento inteiramente casualizado com seis tratamentos e sete repetições, em quatro ciclos de produção de 28 dias/cada. Os tratamentos foram: Controle - 16,92% PB; 0,750% lisina digestível. Tratamentos 1 ao 5, com níveis de PB de 14% e lisina digestível de 0,600; 0,675; 0,750; 0,825 e 0,900%, respectivamente. Os níveis referentes aos tratamentos 1 e 2 (0,546 e 0,640% Met + Cis digestível / 0,600 e 0,675% de lisina digestível) proporcionaram menor tamanho do ovo; em contrapartida os ovos obtiveram maior porcentagem de casca, quando comparados à dieta controle. A exigência de lisina digestível em relação aos demais aminoácidos digestíveis, pode ser estimada em 0,750% em dieta com 14% de PB, o que corresponde ao consumo médio diário de 876 mg lisina dig. ave-1 e 798 mg Met + Cis dig. ave-1 dia-1, sem comprometer o desempenho e qualidade interna e externa dos ovos.
Níveis de lisina digestível para poedeiras semipesadas e seus efeitos sobre a qualidade dos ovos
Keywords: proteína ideal; aminoácidos digestíveis; Isa Brown; exigência; dieta; ideal protein; digestible amino acids; Isa Brown; requirement; diet